Preservasi Bahan Pustaka Menggunakan Teori Piramida Preservasi di Perpustakaan Pascasarjana Universitas Negeri Padang - Sharlino, M. Zacky; Nurizzati, Nurizzati (Lembaga Yasin AlSys, 2024)
This study aims to describe the preservation of library materials, the factors that cause damage, and the obstacles faced by librarians in preserving the Postgraduate Library of Padang State University. The method used is descriptive qualitative data collection techniques through interviews and documentation. The results showed that the preservation activities carried out include cleaning dust, tidying up books, regulating room temperature, and checking collections. Factors causing damage to library materials include environmental factors such as light, biological factors, especially termites and insects, and Human Factors. Constraints faced by librarians in the preservation is the lack of budget, limited library personnel, and lack of complete preservation equipment. It is recommended that libraries improve the implementation of preservation, conduct training for librarians, provide special rooms and funds, and equip preservation equipment as needed.preservation, library materials, damage factors, preservation constraints